INVESTIGATING THE CORRELATION BETWEEN EFL STUDENTS’ PARTICIPATION IN CLASSROOM PRESENTATION AND THEIR ACADEMIC ACHIEVEMENT - Nadya Khusnul Khotimah; Hesti Wahyuni Anggraini (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study investigates the relationship between EFL students' participation in classroom presentations and their academic success, specifically measured by Grade Point Average (GPA). It aims to determine if there is a significant correlation between overall participation in these presentations and GPA, and to identify which specific aspects of participation such as contribution, interaction, preparation, confidence, and willingness—demonstrate the strongest link to GPA. Employing a quantitative correlational design, the research involved a total of 165 EFL students from the English Education Study Program at Sriwijaya University. These participants were carefully selected using stratified random sampling techniques. Analysis, conducted using Spearman's rank-order correlation, revealed a weak yet statistically significant positive correlation between students' overall involvement in classroom presentations and their GPA (r=0.174, p=0.025). Furthermore, among the various dimensions of participation examined, “Contribution” and “Confidence” emerged with weak but statistically significant positive correlations with GPA (r=0.188, p=0.016 for Contribution; r=0.188, p=0.015 for Confidence). These findings suggest that while actively participating in classroom presentations generally benefits academic progress, the quality of students' input and their self-assurance during delivery appear to be more influential factors than mere general readiness or preparatory efforts. The study offers valuable implications for educators, encouraging them to foster more dynamic learning environments that prioritize meaningful student contributions and build confidence during presentations.